INOVASI SOFTWARE UNTUK MEMPERKUAT SISTEM INFORMASI MANAJEMEN PADA BANK SYARIAH - Putri Andriani Jambak; Uzlah Hansel Bahrin Hasibuan; Yuliana; Nurbaiti (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
This research aims to develop a management information system in Islamic banks through software innovation. In this article, this article discusses operating systems, applications and programming languages, as well as the role of strategic management in Islamic banks. In this research, qualitative methods were used. Qualitative methods use qualitative data and describe it descriptively to evaluate social events, phenomena or situations. Operating systems are grouped by user interface into CUI and GUI, with examples such as DOS, UNIX, and Windows. Application systems, which are designed to process data, include various types of software such as desktop and web applications. Programming languages are a means of communication between humans and machines, including algorithms that are the basis for program design. In addition, this article outlines the development of strategic management in Islamic banks, which focuses on the formulation, implementation and assessment of strategies to ensure compliance with sharia principles. In this context, information technology plays an important role in increasing financial efficiency and inclusion. The application of artificial intelligence at Bank Syariah Indonesia shows a positive impact on customer experience and operational efficiency. Sharia financial product innovations were also discussed, highlighting the importance of SWOT analysis and customer relationship management (CRM) strategies in facing competition. Finally, this article notes the challenges Islamic banks face in identifying profitable projects and adapting to developments in digital banking technology.